Moderasi Beragama melalui Tarekat dan Peran Mursyid dalam Mewujudkan Harmoni Sosial - Hasibuan, Armyn; Siregar, Pahri (UIN Sumatera Utara, 2025)
Tariqah, as part of the Sufi tradition, plays a significant role in fostering religious moderation within pluralistic societies. Beyond serving as an individual spiritual practice, tariqah functions as a social space that transmits ethical and moderate religious values. A qualitative approach was employed through literature review and empirical observation of tariqah practices and the role of mursyids in socio-religious life. The analysis focused on the internalization of Sufi values, the dynamics of mursyid roles, and variations in their doctrinal orientations. Values such as balance, self-discipline, compassion, and rejection of extremism are internalized through rituals, religious education, and community activities. Mursyids act as both spiritual guides and social agents who shape followers’ religious orientation and mediate the implementation of moderation. The diversity among mursyids ranging from moderate-adaptive, traditional-conservative, to highly modern demonstrates that tariqah is a dynamic tradition capable of maintaining its Sufi essence while responding to social change. Consequently, tariqah contributes significantly to strengthening religious moderation and social harmony through the integration of spiritual and social dimensions.